دور التعليم الفني في تحقيق التنمية الصناعية الشاملة والمستدامة في مصر - عمارة، أميرة محمد Emarah, Amirah Mohammed (جامعة عين شمس - كلية التجارة, 2020)
يعد تطوير التعليم والتدريب الفني والمهني أحد المحاور الأساسية لاستراتيجية وزارة التجارة والصناعة، المنبثقة من "استراتيجية التنمية المستدامة: رؤية مصر 2030"، حيث تستهدف استراتيجية الوزارة أن تقود التنمية الصناعية عملية النمو الشامل والمستدام. وتهدف هذه الدراسة إلى بحث دور التعليم الفني في تحقيق التنمية الصناعية الشاملة والمستدامة في مصر، في الفترة من 1990 إلى 2018، وذلك باستخدام نموذج متجه الانحدار الذاتي Vector Auto Regression Model (VAR). ويشتمل هذا النموذج على اختبار سببية Granger، ودالة الاستجابة الدفعية، وتحليل التباين. وقد توصلت الدراسة إلى أن هناك علاقة موجبة بين التعليم الفني والقيمة المضافة للصناعة، باعتبارها مؤشرا للتنمية الصناعية الشاملة والمستدامة. كما توصلت إلى أن الأهمية النسبية للتعليم الفني هي الأعلى ضمن الصدمات التي تفسر التغير في القيمة المضافة للصناعة، وذلك في كل من الأجلين القصير والطويل.
The development of technical and vocational education and training is one of the main pillars of the Ministry of Trade and Industry strategy emanating from the "Sustainable Development Strategy: Egypt's Vision 2030", since the Ministry's strategy aims at making industrial development the driving force of the inclusive and sustainable growth process. The objective of this study is to investigate the role of technical education in achieving inclusive and sustainable industrial development in Egypt, in the period 1990-2018, using a Vector Autoregression (VAR) model. The VAR model includes: Granger causality test, impulse response function and variance decomposition. The study concludes that there is a positive relationship between technical education and manufacturing value added, as a measure of inclusive and sustainable industrial development. It also finds that technical education is the most important shock that explains changes in manufacturing value added, in both the short and long run.
Keywords: التعليم الفنى -- التدريب المهنى -- التنمية الصناعية الشاملة -- التنمية المستدامة -- مصر